PENINGKATAN KETERAMPILAN SOSIAL SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) DI SEKOLAH DASAR - Ulia Pratiwi; Muhammad Syahrul Rizal; Lusi Marleni; Putri Hana Pebriana; Iis Aprinawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low social skills of students in the Social Science (IPAS) subject in Grade III at UPT SDN 010 Siabu. One of the solutions to overcome this problem was the application of the Project Based Learning (PjBL) model. The purpose of this study was to determine the planning, implementation, and improvement of students’ social skills through the application of the Project Based Learning (PjBL) model in Grade III students of UPT SDN 010 Siabu in the 2024/2025 academic year, consisting of 21 students. This research employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of two meetings, which included the stages of planning, implementation, observation, and reflection. Data were collected through observation and documentation using observation sheets of teacher and student activities as well as social skills observation sheets. The data were analyzed using quantitative and qualitative techniques. The results showed that students’ social skills in the IPAS subject improved after the implementation of the Project Based Learning (PjBL) model. In the first cycle, students’ social skills were in the “fair” category with an average score of 77, where 13 students achieved mastery with a classical completeness of 62%. In the second cycle, students’ social skills increased to the “good” category with an average score of 84, where 18 students achieved mastery with a classical completeness of 86%. Therefore, it can be concluded that the implementation of the Project Based Learning (PjBL) model can improve students’ social skills in the IPAS subject for Grade III at UPT SDN 010 Siabu.